Effects of water table fluctuation on carbon dioxide and methane emission from a tropical peat soil cultivated with pineapple (Ananas comosus L. Meer.) - Luta, Wendy (2016)
Tropical peatlands are important buffer for climate change as they absorb atmospheric carbon and store large carbon reserve, both above and below ground. Inappropriate drainage and agricultural development on peatlands result in greenhouse gas emissions such as carbon dioxide and methane. This process could shift the peatlands ecosystem from that of carbon sink to carbon source and subsequently expedite the rate of global warming and climate change. The objectives of this study were to: (i) quantify CO2 and CH4 losses in a tropical soil under simulated water table fluctuation and (ii) determine the relationship between depth of water table and CO2 and CH4 losses of a tropical soil cultivated with pineapple. Greenhouse gases emitted from field and lysimeter study were measured using closed chamber method. Soil CO2 and CH4 emitted were captured using closed chamber method after which they were quantified using gas chromatography. Carbon dioxide and CH4 gases were measured in the early morning I, afternoon, evening, midnight, and early morning II to obtain 24 hour CO2 emission. The flux measurements were carried out in July, August, September, and December 2015 for dry and wet seasons, respectively. Soil CO2 emission in the field study was higher compared with that of the lysimeter study with lower water table in the dry period. Soil CH4 emission from the lysimeter study with lower water table was higher compared with that of the field study for the dry period. The moderate temperature fluctuation is related to CH4 emission. Soil CO2 emission from the lysimeter study with high water table was higher compared with that of field study in the wet period. It is believed that higher CO2 emission occurs in low water table as peat soil surface is exposed to oxidation process. The total soil CO2 emission in the dry season during low water table was higher compared with that of wet season meanwhile CH4 emission in the dry season was higher compared with that of wet season during high water table. The total soil CO2 emission in lysimeter during low water table was lower compared with that of high water table meanwhile CH4 emission in lysimeter during low water table was higher compared with that of high water table. Peat soil water table fluctuation does affect the emission of greenhouse gases in pineapple cultivation on tropical peatland. Regardless of season and depth of peat soil water table, CO2 and CH4 emission occurs in pineapple cultivation of peat soils. The finding of this study will contribute to the understanding of the effect of water table management on carbon loss in peat soils under pineapple cultivation.